1998
DOI: 10.1021/ja972467o
|View full text |Cite
|
Sign up to set email alerts
|

Using Mixed Self-Assembled Monolayers Presenting RGD and (EG)3OH Groups To Characterize Long-Term Attachment of Bovine Capillary Endothelial Cells to Surfaces

Abstract: This paper describes surfaces that promote the ligand-directed binding of cells and resist the cellular deposition of adhesive proteins. These surfaces are based on self-assembled monolayers (SAMs) of alkanethiolates on gold that present mixtures of arginine-glycine-aspartate (RGD), a tripeptide that promotes cell adhesion by binding to cell surface integrin receptors, and oligo(ethyleneglycol) moieties, groups that resist nonbiospecific adsorption of proteins and cells. Surface plasmon resonance (SPR) spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
306
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 338 publications
(322 citation statements)
references
References 25 publications
15
306
1
Order By: Relevance
“…235 A range of techniques have been used to micropattern endothelial cells. [236][237][238][239][240][241][242][243] Chen et al 244 found that cell spreading acted as a regulator of proliferation or death in human and bovine capillary endothelial (CE) cells by tightly controlling cell spreading with adhesive microislands of fibronectin; fibronectin was adsorbed on a methyl-terminated alkanethiol SAM, whereas the nonadhesive background consisted of a hexaethylene-glycolterminated alkanethiol SAM (HEG-SAM) that resisted protein adsorption and cell attachment. Cells that were free to spread over large microislands displayed growth, as expected, but the cells that were constrained to limit their spreading to a small island displayed apoptosis.…”
Section: Ve Endothelial Cell Biology On a Chipmentioning
confidence: 99%
“…235 A range of techniques have been used to micropattern endothelial cells. [236][237][238][239][240][241][242][243] Chen et al 244 found that cell spreading acted as a regulator of proliferation or death in human and bovine capillary endothelial (CE) cells by tightly controlling cell spreading with adhesive microislands of fibronectin; fibronectin was adsorbed on a methyl-terminated alkanethiol SAM, whereas the nonadhesive background consisted of a hexaethylene-glycolterminated alkanethiol SAM (HEG-SAM) that resisted protein adsorption and cell attachment. Cells that were free to spread over large microislands displayed growth, as expected, but the cells that were constrained to limit their spreading to a small island displayed apoptosis.…”
Section: Ve Endothelial Cell Biology On a Chipmentioning
confidence: 99%
“…Cell integrins are transmembrane proteins on the cell surface that adhere to the proteins of the ECM such as collagen, fibronectin, or vitronectin. These and other adhesive proteins contain short peptide sequences such as RGD, REDV, YIGSR, PHSRN, KNEED, and PRRARV, [37][38][39][40][41][42][43][44][45][46][47][48][49] which are bound by the integrins to promote cell adhesion, spreading, and proliferation. Although significant work has been done to attach proteins and peptides to metal oxide particles 21 and silicon oxide on Si wafers, 26 relatively little research has been reported on attachment of polypeptides to macroscopic metallic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Grafted polymers and self-assembled monolayers are methods used to introduce functionality to surfaces, as well as establishing a packing density on the surface and specific orientation of the functionality. Polyethylene glycol (PEG), or polyethyleneoxide (PEO), functionalized surfaces are examples of hydrophilic coatings that offer excellent resistance to protein and cellular adhesion as both grafted polymer and SAM films (19,20,21,22,23,24). In contrast, hydrophobic surfaces, such as octadecyltrichlorosilane SAMs, tend to adsorb proteins as a monolayer thick biofilm (25,26,27).…”
Section: Introductionmentioning
confidence: 99%